Ensinar e Aprender em contexto de estágio de Educação Física - Ana Margarida Teixeira Pinto (2021)
present report aims to obtain the Master's degree in Physical Education teaching in Primary and Secondary Education from Faculty of Sport, University of Porto. This document describes the experience of a preservice teacher (the author) in a school environment, where it was constructed a professional identity, as well as skills, which were developed by taking the role of a Physical Education teacher. The teaching practice took place at a private school in Vila Nova de Gaia, with two other colleagues, under the supervision of a cooperating teacher and a teacher educator from the faculty. Many challenges were overcome, both at a professional and personal level. This report describes the path taken, which started with a reality check, where it became evident the importance of the ability to adjust. During the teaching practice, it was possible to get a hold of the school environment and its way of working, as well as the interpersonal relations that exist in the school community. The challenge from being a student to becoming a teacher and the complexity of inciting students into learning were important elements. The school year was peculiar, which led to a new reality full of new challenges and problems that needed to be overcome that were created by the pandemic. Distance learning was established, leading me to develop different teaching methods, to embrace the spirit of adaptation, to become familiar with the new system and, essentially, to promote an efficient school year to the students. There´s also a study about motivation during online learning and in school learning during the pandemic. The results revealed that the strategies adopted by the teachers during in school learning were promoting autonomy during the lessons and teaching methods that were more focused on the student. In online learning, the use of quiz, competition between teams, an active participation from the students in class and negotiation and awareness processes about online learning.